Surgical intervention using ellipse technique in treatment of gynecomastia - Elghotmy, Mohamed Hamdy (International Surgery Journal, 2019)
Background: The objective of the study was to evaluate the outcome of the ellipse technique in 10 Egyptian patients in contrast with state-of-the-art practice cited in the medical literature. Methods: A prospective comparative study was carried out on 10 consecutive patients with grade III (Simon’s classification) gynecomastia presenting to the outpatient clinic at Menoufia university hospital, Menoufia, Egypt during the period during from June 2015 to march 2018. History taking, local examination, radiological examination and laboratories investigation were done. Results: Mean age of patients was 29.3 years. The BMI of the patients ranged from 32.3 kg/m2 to 37 kg/m2 with a mean BMI of 34.82 kg/m2. All patients showed good wound healing when dressings were removed at the 10-day interval. The scars showed maturation at around 10 to 12 months. None of the patients had a major complication such as infection, hematoma, seroma, or nipple-areola complex necrosis. There were no early postoperative complications apart from moderate bruising in 3 patients. Late complications included slowly resolving hypoesthesia in two patients. This was a transient complication that resolved completely. No patient required revision surgery. Conclusions: The technique allows precise control of the final shape and contour of the corrected chest wall with proper positioning of the nipple-areola complex without a residual deformity. It has been shown to yield consistent and reproducible results in this subset of patients in an easy, quick and safe manner. The technique is also easily learned and taught. The resultant scarring is positioned along the lines of least skin tension and is quite inconspicuous and well hidden in patients with excess chest wall hair.